UPAYA PENGEMBANGAN KECERDASAN SPIRITUAL SISWA MELALUI KEGIATAN EKSTRAKURIKULER ROHANI ISLAM DI SMP YAPAN INDONESIA, DEPOK - Gamar Al Haddar (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2016)
This study aims to determine (1) the state of the Islamic spiritual extracurricular activities of SMP Yapan Indonesia. (2) a state of spiritual intelligence in junior high school students of Yapan Indonesia (3) efforts in the development of spiritual intelligence Yapan Indonesian junior high school students through extracurricular activities spiritual Islam. This research was conducted using qualitative research methods. In determining the sample, the researcher use purposive sampling, and the